Systematic Literature Review: Feasibility of Using the E-Modules in ESD-Based Science Learning in Elementary School - Dwinandha Putri, Febrialita Salma; Sujana, Atep; Kirana, Cut Rania; Istiqomah, (International Conference on Elementary Education, 2025)
The level of environmental care attitudes of elementary school students is currently still in the moderate category and not optimal so that integrating environment-based learning through E-Modules into the curriculum can help students understand the importance of ecosystems and the relationship between the environment and humans. This study aims to analyse the feasibility of using E-Modules in ESD-based science learning to train students' environmental awareness. This type of research is a qualitative study using a systematic literature review research design in terms of inclusion and exclusion criteria. Based on the results of the analysis conducted, 4 articles were obtained that could be studied in depth. In the research conducted, it was found that E-Modules on ESD-based science learning can train and improve environmental care attitudes in elementary school students. Recommendations that can be made for future researchers are to develop ESD-based interactive e-modules with interesting learning methods and develop other science materials.